Upaya Meningkatkan Hasil Tanaman Ubi Kayu Varietas Lokal Maluku Utara - Tri Mulya Hartati; Chumidach Roini; Indah Rodianawati (Jurnal Pertanian Khairun, 2022)
The increasein cassava production is aimed at increasing yields that remain high according to needs and demand, therefore the target of increasing the weight of fresh tubers needs to be achieved with the method of development of cultivation technology. This research aims to examine the influence of cuttings sliced models and the number of shoots on the growth and yield of cassava crops. The study used local variety cassava cuttings from Tobelo, North Maluku. The study was arranged in factorial Randomized Block Design, as the first factor is the cuttings sliced model, consisting of 3 levels namely flat slice, one-sided sliced, and two-sided sliced, and the second factor is the number of buds consisting of 3 levels namely one bud, two buds, and three buds. Each treatment is repeated 3 times so there are 27 trial units. The results showed the treatment of the two-sided sliced model provided the highest average value on all observation parameters, while in the treatment of the number of buds, the number of buds one tended to provide the highest average value. The highest cassava production result was obtained in the combination of two-sided sliced model treatment with the number of buds one which is 15.96 tons ha-1.